Online Job Search and Matching Quality - Constantin Mang (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
The Internet has fundamentally changed the way workers and firms are matched on the job market. Compared to newspapers and other traditional employment resources, online job boards presumably lead to better matches by providing a wider choice of job advertisements and more sophisticated methods for finding suitable vacancies. This study investigates the association of online job search and matching quality using individual-level data from the German Socio-Economic Panel (SOEP). My results show that job changers who found their new job online are better matched than their counterparts who found their new job through newspapers, friends, job agencies, or other channels.
Keywords: L86; J64; 330; Internet; job search; matching quality; Arbeitsuche; Internet; Matching; Schätzung; Deutschland